First record of Kermes echinatus on Quercus ilex - Stathas, G. J.; Kartsonas, E. D.; Skouras, P. J. (ENTOMOLOGIA HELLENICA, 2013)
The scale insect Kermes echinatus Balachowsky (Hemiptera, Coccoidea, Kermesidae) was recorded on Quercus ilex in November 2012 in Kalamata and in December of the same year on the same host species in Athens. Quercus ilex is recorded for the first time as the host of this scale. This scale is first recorded in continental Greece. The population of the scale in both areas consisted mainly of first instar nymphs, whereas in Kalamata individuals of the scale in advanced developmental stages were recorded. Preliminary studies indicate that natural enemies are active against K. echinatus. Moultings of larvae and pupae and adults of Chilocorus bipustulatus L. (Coleoptera: Coccinellidae) were found on colonies of the scale. Parasitoid exit holes were recorded on female adults of the scale. Some data on morphology and infestation of the scale on Q. ilex are given.